The Jewish Vanguard : A Cultural Moment - Sjöberg, Sami, (Literature and Cultural Studies E-Books Online, Collection 2026., 2026)
The Jewish Vanguard brings to light a spirited cultural moment when Jewish writers and artists were at the forefront of the avant-garde. Blending literary theory, cultural history, and Jewish studies, this book reveals how these figures reimagined identity, politics, and tradition through radical artistic and intellectual experimentation. From mystical thought to progressive utopias, their ideas resonated far beyond their immediate circles, even as their contributions have been marginalised in mainstream narratives. Featuring original archival research and fresh case studies, The Jewish Vanguard offers a compelling new perspective on Jewish participation on the early 20th-century cultural arena, challenging conventional views and opening new paths in avant-garde and cultural studies.